Optimal location of renewable power - Henrik Bjørnebye; Cathrine Hagem; Arne Lind (Statistics Norway, Research Department, 2017)
A decarbonization of the energy sector calls for large new investments in renewable energy production. When choosing the location for increased production capacity, the producer has typically limited incentives to take fully into account the investments costs of the subsequent need for increased grid capacity. This may lead to inefficient choices of location. We discuss the regulatory background for an integrated EU electricity market, the binding renewable targets, and renewable incentives. We explore analytically the design of feed-in premiums that secure an optimal coordinated development of the entire electricity system. We investigate numerically the potential welfare cost of a non-coordinated development of grids and production capacity in the Norwegian energy system. Our result indicates that grid investment costs can be substantially higher when the location decision is based on private profitability compared with a socially optimal location. However, the difference in the sum of grid investment cost and production cost is much more modest, as location based on private profitability leads to capacity increase in areas with better wind conditions.
Keywords: Q42; Q48; Q58; 330; Energy policy; renewable targets; wind power; location of renewable energy production; feed-in premiums